Juxtaposing generic skills development in collaborative knowledge work competences and related pedagogical practices in higher education - Muukkonen, Hanni; Lakkala, Minna; Ilomäki, Liisa; Toom, Auli (Frontiers in Education, 2022)
This study employs the term knowledge work competence to address generic aspects of higher education graduates’ expected learning outcomes. Twenty-eight higher education courses were investigated: 1069 students responded to the Collaborative Knowledge Practices (CKP) questionnaire to rate their self-evaluated competence development. From the same courses, 56 teachers provided descriptions of the course pedagogical practices. First, students’ self-reported generic collaboration competence gains were analyzed statistically for differences between courses. Second, qualitative categorization of the pedagogical practices based on rich description of pedagogical designs and teachers’ reflective responses was carried out. This offered a categorization with elaborated descriptions and a clustering to three types of enacted pedagogical practices. Finally, the study juxtaposed these previous two results to investigate how the pedagogical features were related to students’ self-evaluations on collaboration competence gains. The findings highlighted one cluster of pedagogical practices, collaborative knowledge creation with systematic support for epistemic and group work, as most beneficial for student competence gains. In it, professional ways of working were explicitly modeled and practiced, teacher support for knowledge creation during contact teaching was available, and time was reserved for reflection with students. Such pedagogical practices are important to ensure graduates’ fluent transition to complex knowledge work.